Efektivitas Penggunaan Media Digital Dalam Pembelajaran Bahasa Arab Di Pesantern Darul Ikhlas Panyabungan Kab. Mandailing Natal - Hasanuddin, Hasanuddin (Scidac Plus, 2024)
This study aims to test the effectiveness of using digital media in Arabic language learning, especially in improving students' understanding of the material and learning motivation. This study uses a quasi-experimental design method, this study involved two groups of students, namely the experimental group that used digital media in learning and the control group that used conventional methods. Data were collected through pre-tests and post-tests to measure understanding of the material, learning motivation questionnaires, and observations during the learning process. The results showed that the experimental group experienced a significant increase in understanding the material, with an average post-test score of 87.5 which was higher than the control group, which was 71.5. In addition, students who learned with digital media also showed higher learning motivation, marked by greater interest and involvement in learning. Although there are obstacles related to device access and internet connectivity, overall digital media has proven to be effective in learning Arabic.